Membangun Personal Branding Pada UMKM Kerupuk Kedelai “Berkah” Melalui Pembuatan Logo dan Kemasan - Zainal Abidin Achmad; Nurul Widji Triana; Dewi Puspa Arum; Zalfa Nurrahmah Agustina; Achmad Derajat Waskito; Zhafira Hanina; Ardhelia Damayanti Wirawan (Institut Nalanda, 2024)
The existence of Medium, Small and Micro Enterprises (MSMEs) in Indonesia has a big role in building the people's economy. So that micro entrepreneurs need to keep up with the times in developing their business. For this reason, knowledge of business actors is needed in forming the characteristics of the business they have, not only from product innovation but the physical condition and quality of a product needs to be developed so that buyers have a good visual of the product to be sold. Kerupuk Kedelai dan Bawang “Spesial” is one of the UMKM that needs to build product branding in order to compete in a wider market share. The activity process takes place using interview and observation methods at the location where it was made directly. Based on the observation results, it was found that these MSMEs need to remake the logo and product packaging to make it more attractive. The process of making logos and product packaging is assisted directly by the community service team by consulting directly with business owners. The creation of a logo and product packaging is the first step of Kerupuk Kedelai dan Bawang “Spesial” in building business branding to compete in the market.